"Sorry does not pay my bills". The Handling of Complaints in Everyday Interaction/Cross-Cultural Business Interaction - Trosborg, Anna; Shaw, Philip (HERMES - Journal of Language and Communication in Business, 1998)
This article is concerned with the teaching of pragmatic functions when training stu-dents for a future career in intercultural business communication. Having outlined six important constellations likely to result in success or failure, we focus on strategies for the successful handling of customer complaints seen in comparison with responses to complaints in everyday interactions. It is suggested that transfer of behaviour con-sidered suitable in everyday face-to-face interaction to business interaction may lead to unsuccessful processing of customer complaints.